Dynamics of the termolecular (HF+HF+HF) reaction - Ibrahim Ali , Noorbatcha (Universiti Malaya, 2006)
The termolecular interaction among three hydrogen fluoride molecules has been modeled as taking place between a hydrogen fluoride dimer (HF)â‚‚ and a hydrogen fluoride molecule. An accurate multi-dimensional potential energy surface (PES) that can fully describe the interaction among the three reacting molecules is still not available. We have overcome this problem by calculating the PES of this system using the London-Eyring-Polanyi-Sato (LEPS) formulation. The energy barriers and well depths are in good agreement with ab initio calculations. We have adopted the quasi-classical trajectory (QCT) method to simulate the dynamics of the six-centered hydrogen bond exchange reaction. In this paper we present our formulation of the QCT approach to simulate this reaction in which over 100,000 trajectories have been computed. Opacity ,functions and reaction cross section for reactive trajectories are reported. We find that the six-centered bond exchange reaction between the three HF molecules do take place but with low probability. Assisted six-centered reactions and monomer exchange reactions also take place to a greater extent. Vibrational excitation of reactants also play an important role in the enhancement of reactivity.